PERLINDUNGAN HUKUM DAN PERAN OJK DALAM MENGAWASI PEMBIAYAAN TERHADAP INVESTASI BODONG - Risa Irnawati; Irvan Bari Alghani; Devia Shafa Salsabila; Endang Kartini Panggiarti (Universitas Kristen Indonesia Toraja, 2023)
The purpose of this research is to examine the role of the Financial Services Authority in combating illegal investments due to the increasing number of illegal investments in Indonesia, which undoubtedly harms many parties, especially those who fall into investment scams. The method used in this research is normative. The sources and types of legal materials used are primary legal materials in the form of legislation (such as the OJK Law, Consumer Protection Law, and related regulations) and secondary legal materials in the form of books and journals related to illegal investments and the Financial Services Authority (OJK).